Occupation and Local Government Administration in Kielce during World War I - Ciosek, Ireneusz (Historia i Polityka, 2025)
The political situation of the inhabitants of Kielce changed with the hostilities of World War I. In the Military General Government of Lublin, on August 18, 1916, a regulation was issued regarding the local government system in 34 cities of the Austrian occupation, including Kielce. The announcement of elections to the city council in 1916 accelerated the city inhabitants’ political maturation process. When the Kielce City Council was established in January 1917, it became a vital civic institution that contributed significantly to the increase in the inhabitants’ social, economic and political activity. Then, the city government was an organized representation towards the occupation authorities, actively working to improve the living conditions of the city inhabitants. National and state demands were formulated at the City Council forum. Many councilors at that time, after regaining independence, actively participated in the local government life of Kielce in 1918–1939.